Child maltreatment during school and childcare closure due to the COVID-19 pandemic - Vermeulen, Samantha (Child maltreatment, 2023)
The aim of the present study was to examine child maltreatment prevalence rates during the first COVID-19 related national closure of schools and childcare settings (the lockdown) in the Netherlands. Based on reports of childcare professionals and primary and secondary school teachers (N = 444) the prevalence of child maltreatment during the 3 months of this first lockdown was estimated at almost 40,000 children, or 14 per 1,000 children. The prevalence of emotional neglect was found to be three times higher during the lockdown compared to a period without lockdown. This significant difference was reflected in overall emotional neglect as well as for two main subtypes of emotional neglect: educational neglect and witnessing domestic violence. No significant differences were found for other types of child maltreatment. Most of the reported cases of maltreatment were already problematic before the lockdown and became worse during the lockdown. The results of this study indicate that the closure of schools and childcare settings may have enormous negative consequences for vulnerable children.